The Effect of Learning Interest and Learning Discipline on Student Learning Outcomes in Informatics Class X SMA Negeri 8 Pontianak - Dewi Sulistiyarini Ismaya; Ferry Marlianto; April Hepytasa; Siti Munfarida; Nadya Aulia; Agustinus Alan Dwitama Putra; Kelvian Nandus Tijak; Estikrilasa (PT. PENERBIT TIGA MUTIARA, 2024)
The world of education is currently developing, various kinds of innovation and renewal are carried out to improve the quality and quantity of education. Various breakthroughs have also been made both in curriculum development, learning innovation, and the provision of educational facilities and infrastructure needed to improve the quality of education itself. The method used in this study is a quantitative descriptive method with an Ex Post Facto approach. The population of this study is class X students of SMA Negeri 8 Pontianak for the 2023/2024 school year.The data collection techniques in this article are direct communication techniques and also use questionnaires. The validity test of the instrument is used to assess whether the instrument can accurately disclose the data of the variable being studied. The validity of the content and construct was assessed through expert assessment by three validators, consisting of two IT lecturers and one Informatics teacher, to evaluate the suitability of the questionnaire about learning interests and learning disciplines. The data from this research includes information about students of SMA Negeri 8 Pontianak class XA, XB, XC, XD, XE, XF, XG, XH, XI which amounted to 322 students who had previously been observed, this was done to find out the problems at SMA Negeri 8 Pontianak before a study was conducted. The research carried out included one bound variable, namely Learning Outcome (Y), and two independent variables, namely Learning Interest (X1) and Learning Discipline (X2) Variable Data for X1 and X2 was obtained from a questionnaire with a likert scale answer model of 4 (four) alternative answers that were distributed according to the sample needs to 167 students who were the research sample.